The Effects of Exercise and Zinc Deficiency on Some Elements in Rats - Baltaci, Abdulkerim Kasim; Gokbel, Hakki; Mogulkoc, Rasim; Okudan, Nilsel; Ucok, Kagan; Halifeoglu, Ihsan (Humana Press Inc, 2010)
The objective of the present study was to determine the effects of exercise and zinc deficiency on some elements in rats. Forty adult male Sprague-Dawley species male rats were allocated to four groups as follows: Group 1: control, Group 2: zinc-deficient, Group 3: exercise in which exercise group fed with a normal diet, Group 4: zinc-deficient exercise, exercise group fed by a zinc-deficient diet for 15 days. After the procedure ended, rats in groups 3 and 4 were exercised on the treadmill for 60 min at a speed of 6 m/min until the exhaustion. The rats were decapitated 48 h after exercise together with their controls, and blood samples were collected to determine copper (Cu), iron (Fe), magnesium (Mg), calcium (Ca), and phosphorus (P) levels. The highest Cu and Fe values in the serum were obtained in group 2 (p < 0.01). The levels of these elements in group 4 were lower than those in group 2 and higher than the levels in groups 1 and 3 (p < 0.01). Serum Mg levels did not differ significantly between groups. Group 4 had the lowest serum Ca and P levels (p < 0.01). These same parameters in Group 2 were higher than those in group 4 but significantly lower than those in groups 1 and 3 (p < 0.01). There was no significant difference between Ca and P levels of groups 1 and 3. The results of the study indicate that zinc deficiency adversely affects copper, iron, calcium, and phosphorus mechanisms and that these adverse effects much more marked after an effort exercise.
Keywords: Exercise; Zinc deficiency; Elements; Rat